A Potential Function for the Power Flow in DC Microgrids: An Analysis of the Uniqueness and Existence of the Solution and Convergence of the Algorithms (2019)
The power flow equations in DC microgrids are nonlinear due to the presence of constant power terminals. In this context, a rigorous demonstration of the convergence and uniqueness of the solution for Newton’s method is required. This problem is particularly important in islanded microgrids, where the power flow method determines the equilibrium point, which in turn is used for other analyses such as stability, optimal operation, and reliability. In this paper, we present a new concept associated with power flow equations, namely the potential function of the power flow. This function allows transforming the power flow problem into an optimization model and uses convex analysis for determining its convergence and the uniqueness of the solution. Being a scalar function, the potential of the power flow can give valuable geometrical insights on the problem. In addition, the optimization approach can be used to solve the power flow problem considering inequality constraints. Simulation results demonstrate the applicability of this approach in practice. © 2019, Brazilian Society for Automatics--SBA.